Stem Cell Culture Collection - Promising Strategy for Animal Genetic Resource Preservation - Guan, Weijun; Li, Xiangchen; Jin, Dapeng; He, Xiaohong; Pu, Yabin; Zhao, Qianjun; Lu, Taofeng; Bai, Chunyu; Wu, Shen; Su, Xiaohua; Ma, Yuehui (IntechOpen, 2011)
None